MAKNA STIGMA SOSIAL BAGI DISABILITAS DI DESA SEMEN KECAMATAN PARON KABUPATEN NGAWI - Widyastutik, Cahyani (Paradigma, 2021)
ABSTRACT Social stigma is a behavior where a person is not accepted in a group due to the belief that the person is against existing norms. Social stigma can lead to exclusion from a person or group. This research is basically motivated by the occurrence of stigma against people with disabilities in Ngawi Regency. The occurrence of disability stigma is certainly caused by various factors that influence it. In this study itself also took the focus of research on the meaning of stigma for disabilities. This study uses Edmund Husserl’s phenomenological theory analysis regarding the meaning of stigma based on the experience of disabilities. This study uses qualitative methods by collecting data in the form of observation, interviews and documentation. From the results of the research process, it can be concluded that the factors causing the stigma of disability are none other than physical limitations. The forms of disability stigma include bullying, insults and even 2 discrimination. Disabilities who are stigmatized do not always feel humiliated because they themselves have their own meaning about the stigma they face. Keywords: Stigma, Disability, Meaning